Гуни напередодні їх вторгнення в Європу - Павленко, Ю.В.; Смагулов, Є.А. (Археологія, 1993)
У статті розглядається проблема етногенезу та локалізації політичних центрів гунського об'єднання напередодні їх вторгнення в степи Східної Європи. На основі археологічних та писемних джерел доводиться, що в ІІІ—IV ст. гунське об'єднання складалось на території сучасного Казахстану, між Східним Приараллям та Західним Тянь-Шанем. Одним из принципиально важных, но пока все еще слабо разработанных вопросов древней и раннесредневековой истории Украины, Южной России, Казахстана и Средней Азии является проблема этногенеза и политических объединений гуннов. Комплексное исследование археологических и письменных источников позволяет в общих чертах проследить исторические судьбы этого народа. Во II в. часть разгромленных у границ Китая северных сюнну переселяется на запад, в предгорья Тянь-Шаня и Каратау, входит в политическую систему государства Кангюй (на средней Сырдарье) и осваивает степи южного Казахстана. Со временем, смешавшись с местным населением, часть их занимает Северо-Восточное Приаралье, подчиняет местные тюркоязычные племена болгар и со средины IV в. начинает совершать далекие походы на запад, побеждая алан и готов. Переселение части гуннов в восточноевропейские степи имело место уже в первой половине V в. Параллельно этому гунны предгорных долин устанавливают гегемонию в пределах Средней Азии и к началу VI в. распространяют свою власть на сопредельные области Афганистана, Восточного Туркестана и Северной Индии. Однако, как в Европе, так и в Азии время гуннского господства было непродолжительным и к середине VI в. они сходят с исторической арены, уступая первенство другим народам. Походы гуннов в Восточную и Центральную Европу обусловили крушение готского владычества в Северном Причерноморье и в конечном счете способствовали славянскому продвижению в Подунавье. One of the fundamentally important but still poorly developed problems of the ancient and early medieval history of the Ukraine, South Russia, Kazakhstan and Central Asia is the problem of ethnogenesis and political unification of Huns. Comprehensive examination of archaeological and written sources permits to follow in outline the historic fortunes of this
nation. In the 2 nd century part of the northern S’unnu people having been defeated at the borders of China migrated to the West, to the foothills of Tianjin and Karatau, entered the political system of the Kangyui state (on the mid-Syr Darya river) and developed South Kazakhstan steppes. In due course, having fused with the local population, part of them occupied north-east Aral Sea area, subdued local Turkic speaking tribes of Bulgarians and starting the mid-IV century made raids far to the West conquering Alans and Goths. Partial migration of huns to the east European steppes was already observed in the early half of the V century. At the same time huns living in the foothill valleys established their hegemony within the Central Asia and by the early VI century extended their power to the contiguous areas of Afghanistan, eastern Turkestan and north India. However, huns’ domination both in Europe and Asia was short, and by the mid-VI century they dropped out of historial arena conceding the first place to other nations. Raids of Auns to the Eastern and Central Europe stipulated the downfall of the Gothic rule in the Nort Pontic area and finally promoted the Slav advancement to the Danube basin areas.